(NbIOHIMIQ (B2-(NTOMs (NU^EBNIK s - P.(Na(B.(NsOBIROWA s; (Nn(B.(Nm(B.(N`LDA[EW s ((NtA[KENT s "IJOD-PRINT ", 2020)
(Nw NASTOQ]EM U^EBNIKE IZLOVENY OSNOWOPOLAGA@]IE PRINCIPY FUNDAMENTALXNOJ BIOHIMII I MOLEKULQRNOJ BIOLOGII(B.s
Keywords: Biokimyo 1-qism